L’action en classe de langues et les activités de recherche en didactique des langues et des cultures - Georges Daniel Véronique (Recherches en didactique des langues et des cultures)
This paper is devoted to a discussion of the nature of language and culture didactics. The methodology and implications of research action in the field of language teaching is examined. The issue of second language classroom research is analyzed in the French context.